Cardiac and Aortic Modifications After Endovascular Repair for Blunt Thoracic Aortic Injury: A Systematic Review. (August 2022) - Mandigers, Tim J.; Bissacco, Daniele; Domanin, Maurizio; D'Alessio, Ilenia; Tolva, Valerio S.; Piffaretti, Gabriele; van Herwaarden, Joost A.; Trimarchi, Santi
Abstract : Objective: Blunt thoracic aortic injury (BTAI) is a devastating condition that commonly occurs in healthy and young patients. Endovascular treatment is the first choice; however, it has also been demonstrated to alter cardiovascular haemodynamics. The aim of this systematic review was to describe the cardiovascular modifications after thoracic endovascular aortic repair (TEVAR) for BTAI. Data Sources: PubMed (MEDLINE), Scopus, and Web of Science were systematically searched for eligible studies reporting on modifications in aortic stiffness, blood pressure, cardiac mass, and aortic size. Review Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was followed. The Newcastle–Ottawa Scale was used to assess the methodological quality of included studies. Results: A total of 12 studies reporting on 265 patients were included. Severe heterogeneity existed among the included studies with regard to demographics, BTAI grade, endograft specifications, reported outcomes, and the method of evaluation. Regarding aortic stiffness, two studies found a significant increase in pulse wave velocity (PWV) in patients after TEVAR compared with a control group, while one did not find a significant increase in PWV and augmentation index after > 3 years of follow up. Five studies reported an increase in the incidence of post-TEVAR hypertension up to 55% (range 34.8% – 55.0%) vs. baseline. One study found a statistically significant increase in left ventricular mass and left ventricular mass index during follow up. Nine studies report data regarding aortic dilatation or remodelling after TEVAR. One found a 2.4 fold faster growth rate in ascending aortic diameter vs. controls, while other studies described significant changes in aortic size at different locations along the aorta and endograft after TEVAR. Conclusion: This systematic review highlights adverse cardiac and aortic modifications after TEVAR for BTAI. The results stress the need for lifelong surveillance in these patients and the necessity of developing a more compliant endograft to prevent cardiovascular complications in the long term.